Long-lasting effects of experimental flow intermittency on alpine stream macroinvertebrates (Val Roseg, Switzerland) - Annemieke M. Drost; Andre R. Siebers; Amael Paillex; Benjamin Misteli; Edwin T. H. M. Peeters; Christopher T. Robinson (Hydrobiologia, 2022)
Changing weather patterns and receding glaciers are predicted to increase flow intermittency in alpine streams. If aquatic macroinvertebrate communities largely comprise taxa adapted to perennial flows, an increase in flow intermittency substantially reduces biodiversity and affects functional processes. We conducted a before-after-control-impact field experiment to examine how macroinvertebrate communities in an alpine headwater stream responded to and recovered from a repeated experimental increase in flow intermittency. Flow in one channel was manipulated to simulate increased summer intermittency (June–September) over two consecutive years, whilst an adjacent channel served as a control. We monitored the density of benthic macroinvertebrates, periphyton and organic matter at approximately monthly intervals over three years during the snow-free period. Before manipulation, both channels had similar ecological properties. The flow manipulation reduced the overall macroinvertebrate density, and especially the proportional rheophile density, across both years. Recovery of the macroinvertebrate community following experimental flow intermittency took more than a year, and longer than our study period. This could be due to long aquatic life stages, dispersal limitation and biotic interactions. We conclude that climate-induced changes in alpine stream flow regimes can lead to a fundamental shift in macroinvertebrate assemblages through local extinctions, mostly of rheophilic species.